Humanism and Poetic Discourse: An Analysis of Shaikh Nur ud-Din's Contribution (International Journal of Food and Nutritional Sciences, 2022)
Kashmir is well known to the world from the very earliest times, because of its geographical features, culture, civilization and its people. It is for this reason that right from the ancient times the Valley of Kashmir has attracted the attention of large number of people including the Sufis, Rishis, Sayyids, Ulama, poets, learned men and travelers. The coming of these people in Kashmir gave rise to new ideas and philosophies. One among these philosophies was Reshi Movement. The credit of this indigenous movement in Kashmir goes to Shaikh Nur-ud din(r.a). He is regarded the patron of this movement. Shaikh Nur-ud-din Noorani (R.A), celebrated saint of Kashmir, is known by many names